The Effect of Internal Audit on The Prevention of Fraud - Delina Pitriani; Shinta Dewi (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
This study aims to determine the effect of internal audits on fraud prevention. The formulations in this study are has the internal audit at the Selaawi Garut Unit Bank (BRI) adequately, does internal audit affect the prevention of fraud in the bank (BRI) Selaawi Garut Unit. The research method in this study is to use quantitative methods. The object of research is internal audit and fraud prevention. The dependent variable is Fraud Prevention, while the independent variable is Internal Audit. The research population is all employees who work at Bank BRI Unit Selaawi Garut, as many as 31 people. Samples were taken randomly from as many as 31 people. Data analysis used simple linear regression. The results showed that Internal Audit affected Fraud Prevention. Furthermore, the internal audit department personnel must enhance the caliber of their analytical procedures in the context of fraud auditing, preliminary surveys, program audits, and auditor team selection. This finding will enable future researchers to replicate the study by incorporating additional variables.